2016
DOI: 10.5847/wjem.j.1920-8642.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal ketamine for the treatment of patients with acute pain in the emergency department

Abstract: BACKGROUND: Pain in the emergency department (ED) is common but undertreated. The objective of this study was to examine the effi cacy and safety of intranasal (IN) ketamine used as an analgesic for patients with acute injury with moderate to severe pain. METHODS:This study was a cross sectional, observational study of patients more than 8 years old experiencing moderate to severe pain [visual analog score (VAS) >50 mm]. The initial dose of IN ketamine was 0.7 mg/kg with an additional dose of 0.3 mg/kg if VAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 19 publications
2
17
1
1
Order By: Relevance
“…Even though there are multiple observation trials studying ketamine, the literature supporting it as an alternative to opioids for the management of acute pain is limited by the low quality of study design and small numbers of studies, although newer studies are overcoming these issues . In many instances, the inclusion criteria were either very broad and included patients that probably should not have received either an opioid or ketamine or compared ketamine to a placebo, a questionable study design considering we have effective analgesics .…”
Section: Discussionmentioning
confidence: 99%
“…Even though there are multiple observation trials studying ketamine, the literature supporting it as an alternative to opioids for the management of acute pain is limited by the low quality of study design and small numbers of studies, although newer studies are overcoming these issues . In many instances, the inclusion criteria were either very broad and included patients that probably should not have received either an opioid or ketamine or compared ketamine to a placebo, a questionable study design considering we have effective analgesics .…”
Section: Discussionmentioning
confidence: 99%
“…Andolfatto G, et al [15] used Intranasal ketamine for analgesia in the emergency department in a study and have reached a conclusion that intranasal ketamine lowered VAS pain scores to a clinically significant degree in 88% of emergency department (ED) patients Also Roshana S, et al [16] tried intranasal ketamine for the treatment of patients with acute pain in the ED and concluded that intranasal ketamine is an analgesic choice for acute injury patients with moderate to severe pain especially in an overcrowded and resource limited ED.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine safety has been probed in a variety of clinical studies. One study that evaluated intranasal ketamine for pain control in an emergency department setting cited concerns about ketamine safety [83]. The study concluded that, based on a visual analog pain score, most of the study subjects received pain relief from the ketamine [83].…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
“…One study that evaluated intranasal ketamine for pain control in an emergency department setting cited concerns about ketamine safety [83]. The study concluded that, based on a visual analog pain score, most of the study subjects received pain relief from the ketamine [83]. At the same time, they noted only mild or transient side effects in this population [83].…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
See 1 more Smart Citation